2001
DOI: 10.1016/s0014-5793(01)03177-5
|View full text |Cite
|
Sign up to set email alerts
|

Substrate specificity and subsite mobility in T. aurantiacus xylanase 10A

Abstract: The substrate specificity of Thermoascus aurantiacus xylanase 10A (TAX) has been investigated both biochemically and structurally. High resolution crystallographic analyses at 291 K and 100 K of TAX complexes with xylobiose show that the ligand is in its K K anomeric conformation and provide a rationale for specificity on p-nitrophenyl glycosides at the 3 31 and 3 32 subsites. Trp 275, which is disordered in uncomplexed structures, is stabilised by its interaction with xylobiose. Two structural subsets in fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 40 publications
2
48
0
1
Order By: Relevance
“…For the TaXyn10A structure it was concluded that if the À1 subsite xylose were in the b-configuration, a steric clash would likely induce ring strain, with implications for catalysis. The authors further suggested that the a-configuration as observed in TaXyn10A and now PbXynA1CD, is due to the enzyme selecting the anomeric configuration that most resembles the covalent intermediate step of the double-displacement mechanism (Lo Leggio et al, 2001). Our structure analysis of PbXynA1CD supports these earlier findings and their conclusions.…”
Section: Coordination Of Megx 3 In the Glycone Subsitessupporting
confidence: 87%
See 1 more Smart Citation
“…For the TaXyn10A structure it was concluded that if the À1 subsite xylose were in the b-configuration, a steric clash would likely induce ring strain, with implications for catalysis. The authors further suggested that the a-configuration as observed in TaXyn10A and now PbXynA1CD, is due to the enzyme selecting the anomeric configuration that most resembles the covalent intermediate step of the double-displacement mechanism (Lo Leggio et al, 2001). Our structure analysis of PbXynA1CD supports these earlier findings and their conclusions.…”
Section: Coordination Of Megx 3 In the Glycone Subsitessupporting
confidence: 87%
“…In the case of Cellvibrio mixtus Xyn10B (CmXyn10B) (PDB code: 1UQZ) (Pell et al, 2004b), a catalytic nucleophile mutation to a serine prevents meaningful comparison. The glycone region of native Thermoascus aurantiacus xylanase A (TaXyn10A) (PDB code: 1GOR) contains X 2 with the À1 subsite xylose in an a-anomeric conformation and similar coordination position as observed for MeGX 3 -bound PbXynA1CD (Lo Leggio et al, 2001). For the TaXyn10A structure it was concluded that if the À1 subsite xylose were in the b-configuration, a steric clash would likely induce ring strain, with implications for catalysis.…”
Section: Coordination Of Megx 3 In the Glycone Subsitesmentioning
confidence: 95%
“…The active site search was carried out in the xylan binding pocket of the xylanase from Thermoascus aurantiacus (TAX) (19); multiple active site configurations were identified. One of the best scoring active sites included the wild-type glutamate at position 237, which is predicted to serve as a general base for the reaction and adopts a conformation similar to that seen in the crystal structure of wild-type TAX.…”
Section: Resultsmentioning
confidence: 99%
“…This hydrogen atom fits neatly into a pocket comprising W316 and W324 ( Fig. 5; 1R87 numbering), which is part of a highly conserved tryptophan cage [42,46]. Three contacts under 3 A were identified between the 5b equatorial hydrogen at subsite À1 and XT6 residue W324.…”
Section: X2: Binding Of Wild-type Versus E159q Xt6mentioning
confidence: 98%